AutoCAD 2012 for dummies - Byrnes, David (Hoboken, New Jersey : Wiley Publishing Incorporation, 2011)
A full-color guide to the #1 architectural drafting program AutoCAD 2012! AutoCAD is the leading software used to create 2D and 3D technical drawings. Used by engineers, architects, and drafting professionals, it can be complex and is a perfect subject for the tried-and-true For Dummies format. Overview: A full-color guide to the #1 architectural drafting program-AutoCAD 2012!. AutoCAD is the leading software used to create 2D and 3D technical drawings. Used by engineers, architects, and drafting professionals, it can be complex and is a perfect subject for the tried-and-true For Dummies format. Full-color illustrations make the instructions even easier to follow, because examples in the book appear exactly as they will on the screen. Explains AutoCAD and gets readers quickly up to speed on the latest version; Features full-color illustrations that look the same as the AutoCAD 2012 screens, making the interface and the all-important Model view easier to understand; Covers all the new features, creating a basic layout, using AutoCAD DesignCenter, drawing and editing, working with dimensions, adding text, and more Newcomers to AutoCAD will easily master the software with help from this full-color edition of AutoCAD 2012 For Dummies.
Bender: -- Visualizing the digital world -- Adding lighting -- Default lighting -- User-defined lights -- Sunlight -- Creating and applying materials -- Defining a background -- Rendering a 3D model -- Part 6: -- Part Of Tens: -- Ten Great AutoCAD Resources: -- Autodesks's feedback community -- Autodesk's discussion groups -- Autodesk's own bloggers -- Autodesk university -- Autodesk channel on YouTube -- World wide (CAD) web -- Your local ATC -- Your local user group -- AUGI -- Books -- Ten Differences Between AutoCAD And AutoCAD LT: -- Price -- 3D abilities -- Customization options -- Network licensing -- Express tools -- Parametrics -- Standards checking -- Data extraction -- MLINE versus DLINE -- Profiles -- Reference manager -- Ten System Variables To Make Your Life Easier: -- APERTURE -- DIMASSOC -- MENUBAR -- MIRRTEXT -- OSNAPZ -- PICKBOX -- REMEMBERFOLDERS -- ROLLOBERTIPS -- TOOLTIPS -- VISRETAIN -- Index.
Includes index.
Keywords: AutoCAD